The effect of a novel square-profile hand rim on propulsion technique of wheelchair tennis players - de Groot, S.; Bos, F.; Koopman, J.; Hoekstra, A. E.; Vegter, R. J. K. (Applied Ergonomics, 2018)
Highlights Wheelchair tennis players propel the wheelchair with a racket in the hand. The interface between the wheelchair tennis player and wheelchair is not optimal. A square-profile hand rim (SPR) was developed for wheelchair tennis. The SPR did not improve the propulsion technique when propelling the wheelchair. Study results gave input for new hand rim designs for wheelchair tennis.